The role of work-family conflict in mediating the influence of social support on the psychological well-being of career women - Rabbani, Daffa; Yuniardi, Muhamad Salis (University of Muhammadiyah Malang, 2024)
As time progresses, the participation of women in the workforce is no longer considered taboo. Psychological well-being has become a focal point for experts due to its crucial role for career women. However, achieving it poses a challenge, especially for those with dual roles as employees and spouses/mothers. Efforts to enhance psychological well-being can be achieved through good social support. This research explores the role of work-family conflict as a mediator in the influence of social support on the psychological well-being of career women. The study employed a quantitative cross-sectional approach with purposive sampling techniques. The subjects consisted of 248 permanent female employees with families, and they were measured using the Multidimensional Scale of Perceived Social Support, Work-Family Conflict Scale, and Psychological Well-Being Scale. Furthermore, mediation analysis was conducted using Hayes's PROCESS model 4. The results indicate that social support has a direct and indirect impact on psychological well-being (β =1.27; LLCI = 1.16; ULCI = 1.39) and also influences it indirectly through work-family conflict (β = 0.35; LLCI = 0.18; ULCI = 0.48). The findings emphasize the role of environmental support in the psychological well-being of career women.